Sources of Knowledge and Innovation: An Empirical Text at a Pan-European Regional Level - Jose M. Barrutia; Carmen Echebarria (European Regional Science Association (ERSA), 2013)
Innovation performance seems to rely on efficiently integrating and extending different pieces of various types of knowledge emerging from diverse external sources. Different research traditions have stressed both formal (FSK) and informal sources of knowledge (ISK) as innovation performance drivers. Thus, context-led views such as the innovative milieux approach, innovation systems literature and the knowledge spillover view have tended to focus on diverse, informal and location-facilitated sources of knowledge. Meanwhile, firm-led perspectives such as the innovator networks approach and the open innovation model have tended to emphasise formal, proprietary and well-structured collaboration agreements. However, regardless of the emphasis put on one or other sources of knowledge, the different research traditions seem to agree that both should be important for innovation purposes. We study the combined effect of formal (FSK) and informal sources of knowledge (ISK) on European regional innovation performance. Our findings show that the effect of both sources of knowledge on innovation performance is not simple and linear. First, both sources of knowledge prove to have an interaction effect on innovation performance (i.e. the effect of FSK on regional innovation depends on the level of access to ISK in the region, and vice versa). Second, while the effect of ISK is linear (although different for each region), the effect of the FSK (which are more intensive in monetary costs, time, effort and opportunity costs) has a diminishing returns form, and achieves a saturation point at high levels of use of FSK. Our findings also show that the balanced access to both types of sources is important and that, for instance, regions with limited access to ISK should not expect miraculous effects from high levels of FSK. To the best of our knowledge, previous research has not been reported that has empirically studied the combined effect of both sources of knowledge at a European regional level.
Keywords: 330; European regions; innovation performance; formal sources of knowledge; informal sources of knowledge